2013
DOI: 10.1590/s0102-33062013000300001
|View full text |Cite
|
Sign up to set email alerts
|

Floristic diversity of the soil weed seed bank in a rice-growing area of Brazil: in situ and ex situ evaluation

Abstract: The objective of this study was to compare the ex situ and in situ floristic diversity of the soil weed seed bank of a rice field in northeastern Brazil. In a rice field in the county of Bacabal, located in the state of Maranhão, thirty 25-m 2 plots were laid out. From 15 plots, soil samples (6/plot; n = 90) were taken with a soil probe (25 × 16 × 3 cm) and placed in aluminum trays in the greenhouse. From the remaining 15 plots, weed samples (6/plot; n = 90) were taken with the same soil probe. The number of s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
17
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 62 publications
(22 citation statements)
references
References 26 publications
4
17
0
1
Order By: Relevance
“…And that the greatest species diversity occurred in Alto Alegre do Pindaré, probably due to two areas subject to flooding, which provided more favorable conditions for weeds, and/or the larger sample area relative to Buriticupu. Similar values for floristic diversity were obtained by Mesquita et al (2013) and Silva et al (2014) in upland rice cultivation in the cutting and burning system in areas located in the humid tropic region of the Brazilian state of Maranhão. …”
Section: (A) (B)supporting
confidence: 86%
See 4 more Smart Citations
“…And that the greatest species diversity occurred in Alto Alegre do Pindaré, probably due to two areas subject to flooding, which provided more favorable conditions for weeds, and/or the larger sample area relative to Buriticupu. Similar values for floristic diversity were obtained by Mesquita et al (2013) and Silva et al (2014) in upland rice cultivation in the cutting and burning system in areas located in the humid tropic region of the Brazilian state of Maranhão. …”
Section: (A) (B)supporting
confidence: 86%
“…This result is consistent with that obtained by Silva et al (2014) when studying a weed seed bank in rice crops in the municipality mentioned, where the Cyperaceae family also presented great diversity of species. Mesquita et al (2013), also in a rice bank seed study in the central region of the state of Maranhão, have identified this family with great species richness. Touré et al (2013) have verified the importance of this family in rice cultivation in northern Guinea.…”
Section: Resultsmentioning
confidence: 86%
See 3 more Smart Citations